2021
DOI: 10.3389/fpsyt.2021.618108
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Test Anxiety, Self-Efficacy, and Mental Images Among University Students: Results From an Online Survey

Abstract: Background and Objectives: A substantial portion of students report test anxiety, and those reporting low levels of self-efficacy seem to be especially affected. Previous research has indicated the relevance of mental images in the maintenance of anxiety disorders, however, no data are available with respect to test anxiety. In order to close this gap, the present study investigates the association between test anxiety, self-efficacy and mental images.Method: One hundred sixty-three university students complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 55 publications
0
7
0
2
Order By: Relevance
“…From a psychological perspective, individual factors such as anxiety 9 , motivation 10 , and self-efficacy play critical roles in the manifestation of SR. However, isolating these variables without considering the broader context may lead to incomplete or ineffective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…From a psychological perspective, individual factors such as anxiety 9 , motivation 10 , and self-efficacy play critical roles in the manifestation of SR. However, isolating these variables without considering the broader context may lead to incomplete or ineffective interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is a psychological condition characterized by excessive worry, fear, and physiological symptoms experienced before, during, or after an examination (Torbjørnsen et al, 2021). In the context of nursing education, test anxiety can be particularly detrimental, as it may hinder a student's ability to effectively demonstrate their knowledge and skills in high-stakes exams (Maier et al, 2021). The results of our study indicated that students had an average level of test anxiety as they reported their thoughts of how poorly doing compared with other students and some of them agreed to have a heart beating fast, uneasy, upset feeling when they take an exam.…”
Section: Discussionmentioning
confidence: 99%
“…So, it is illustrated in the results of the present study that students confidently understand and master the basic concepts as well as difficult material taught to them. Undeniably, the curriculum, teaching methods, and assessment practices play a significant role in shaping self-efficacy (Maier et al, 2021). So, nursing faculty can enhance students' motivation and their belief in their success by fostering positive self-beliefs through self-reflection and self-assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por exemplo, sabe-se que a ansiedade avaliativa pode ser afetada por fatores situacionais em torno da avaliação, como as percepções dos alunos sobre a competência acadêmica; no qual, percepções mais baixas de competência estão associadas a níveis mais elevados de ansiedade de provas (Ewell et al, 2022). Isto pode ser explicado pelo fato de níveis elevados de ansiedade de provas prejudicarem a aquisição eficiente do conhecimento durante a preparação para uma prova (Maier et al, 2021). Como resultado da preocupação com o fracasso, as pessoas ansiosas por testes tornamse tendenciosas no processamento de informações relacionadas a ameaças.…”
Section: Introductionunclassified